In vitro antioxidant properties and GC-MS analysis of solvent extracts of Sida acuta leaf - Akeem Adewale Yusuff; Temidayo Ogunmoyole; Mary Ronke Ogundare (Islamic Azad University, Shahrekord Branch, 2023)
Background & Aim: Active search for plants with diverse antioxidant and pharmacological properties capable of counteracting the deleterious effects of free radical-mediated pathologies, is still evolving. The current study investigates the phytochemical screening, antioxidant mechanisms and gas-chromatography-mass spectrometer (GC-MS) analysis of leaf extract of Sida acuta. Experimental: Powdered leaves of the plant was extracted in ethanol, methanol and water. Total phenolic and flavonoids contents of the extracts were measured using established protocols. Also, free radical scavenging activity against 2, 2-diphenyl-1-picryl hydrazyl (DPPH) and nitric oxide radicals (NO•.) as well as the ferric reducing antioxidant power (FRAP) assay were also evaluated. Furthermore, the structure and relative abundance of bioactive compounds in the methanolic leaf extract of Sida acuta was determined on GC-MS. Results: Results indicated that the total phenol and flavonoids content is significantly (P<0.05) higher in methanolic extract when compare with extracts from other solvents. Additionally, DPPH radical scavenging potency and FRAP of the extract is in the order; methanolic> aqueous> ethanolic, while the aqueous extract elicits significant NO• radical scavenging properties when compared with other solvents. The GC-MS chromatogram of the methanolic leaf extract of the plant reveals the presence of 23 bioactive compounds. Taking together, the relative abundance of phytochemical contents and antioxidant capacity of Sida acuta leaves is partly contingent on the choice of extraction solvent. Recommended applications/industries: The presence of various bioactive compounds justifies the use of the plant for diverse remedies in traditional medicine and the need for further studies.